Analisis kesulitan siswa dalam menyelesaikan soal AKM materi SPLDV kelas VIII SMPI Annuriyah Malang - Nur'aini, Luthfiah Hamidah (Maliki Interdisciplinary Journal, 2024)
This study aims to analyze and describe the difficulties of grade VIII students of SMPI Annuriyah Malang in solving AKM problems of Two Variable Linear Equation System (SPLDV) material. The method used was qualitative descriptive with three students selected based on different ability levels. Data was collected through AKM test questions and interviews. The results showed that students' difficulties were divided into three categories: difficulty concepts, principles, and skills. High-ability students have difficulty in algebraic operations, moderate-ability students face principle difficulties in applying elimination methods, and low-ability students have difficulty in understanding the basic concepts of SPLDV. This research also provides several solutions to minimize student difficulties, such as providing stimulus in the form of perception, varied question exercises, and the application of contextual learning strategies. Other solutions include brief verbal comprehension to help students translate SPLDV AKM problems into mathematical models.